Significant differentiation in the apolipoprotein(a)/lipoprotein(a) trait between chimpanzees from Western and Central Africa. Issue 9 (3rd July 2017) - Noureen, Asma; Ronke, Claudius; Khalifa, Mahmoud; Halbwax, Michel; Fischer, Anne; André, Claudine; Atencia, Rebeca; Garriga, Rosa; Mugisha, Lawrence; Ceglarek, Uta; Thiery, Joachim; Utermann, Gerd; et al.
Abstract : Elevated Lipoprotein(a) (Lp(a)) plasma concentrations are a risk factor for cardiovascular disease in humans, largely controlled by the LPA gene encoding apolipoprotein(a) (apo(a)). Lp(a) is composed of low‐density lipoprotein (LDL) and apo(a) and restricted to Catarrhini . A variable number of kringle IV (KIV) domains in LPA lead to a size polymorphism of apo(a) that is inversely correlated with Lp(a) concentrations. Smaller apo(a) isoforms and higher Lp(a) levels in central chimpanzees ( Pan troglodytes troglodytes [PTT]) compared to humans from Europe had been reported. We studied apo(a) isoforms and Lp(a) concentrations in 75 western ( Pan troglodytes verus [PTV]) and 112 central chimpanzees, and 12 bonobos ( Pan paniscus [PPA]), all wild born and living in sanctuaries in Sierra Leone, Republic of the Congo, and DR Congo, respectively, and 116 humans from Gabon. Lp(a) levels were severalfold higher in western than in central chimpanzees (181.0 ± 6.7 mg/dl vs. 56.5 ± 4.3 mg/dl), whereas bonobos showed intermediate levels (134.8 ± 33.4 mg/dl). Apo(a) isoform sizes differed significantly between subspecies (means 20.9 ± 2.2, 22.9 ± 4.4, and 23.8 ± 3.8 KIV repeats in PTV, PTT, and PPA, respectively). However, far higher isoform‐associated Lp(a) concentrations for all isoform sizes in western chimpanzees offered the main explanation for the higher overall Lp(a) levels in this subspecies. Human Lp(a) concentrations (mean 47.9 ± 2.8 mg/dl) were similar to those in central chimpanzees despite larger isoforms (mean 27.1 ± 4.9 KIV). Lp(a) and LDL, apoB‐100, and total cholesterol levels only correlated in PTV. This remarkable differentiation between chimpanzees from different African habitats and the trait's similarity in humans and chimpanzees from Central Africa poses the question of a possible impact of an environmental factor that has shaped the genetic architecture of LPA . Overall, studies on the cholesterol‐containing particles of Lp(a) and LDL in chimpanzees should consider differentiation between subspecies. Abstract : Mean Lp(a) levels in western chimpanzees in Sierra Leone are threefold higher than in central chimpanzees or humans in Central Africa. The underlying genetic architecture of this quantitative trait suggests local adaptive evolution.